2003
DOI: 10.2134/agronj2003.1352
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Soil Water and Solute Transport—Fast, Simplified Numerical Solutions

Abstract: near the soil surface, in response to biology, climate, and management (Gupta et al., 1991). Uptake of water Modeling of water and solute transport in soils is increasinglyand solutes by plants is another difficult area, and ongoimportant in hydrology and agriculture, but there remain many gaps ing research will change the modeling of these processes. and unresolved issues. One of these, the speed and robustness of numerical solutions, is important in large-scale and stochastic model-Not all progress, however,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
161
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 122 publications
(163 citation statements)
references
References 12 publications
1
161
0
1
Order By: Relevance
“…Varado et al [23] assessed the efficiency of Ross model by comparing it at a first step with two analytical solutions and at a second step with SIPAT model. The results of this study showed that Ross solution [10] is a robust and accurate solution while a finer discretization is required close to soil surface to improve the results of cumulative infiltration. Crevoisier et al [24] compared within their study the Ross model with a finite element based Hydrus 1D model to evaluate the accuracy, computing time and convergence quality.…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…Varado et al [23] assessed the efficiency of Ross model by comparing it at a first step with two analytical solutions and at a second step with SIPAT model. The results of this study showed that Ross solution [10] is a robust and accurate solution while a finer discretization is required close to soil surface to improve the results of cumulative infiltration. Crevoisier et al [24] compared within their study the Ross model with a finite element based Hydrus 1D model to evaluate the accuracy, computing time and convergence quality.…”
Section: Introductionmentioning
confidence: 91%
“…Ross [10] proposed a fast and non-iterative solution to solve the Richards' equation. A common way of characterizing unsaturated flow is Richards' equation on its mixed form (Richards, 1931): [29] for retention function is given by the following formula:…”
Section: Ross (2003) Solutionmentioning
confidence: 99%
See 3 more Smart Citations